Drought resistance of spring wheat varieties (Mongolian Journal of Agricultural Sciences, 2019)
Selection for drought tolerance typically involves evaluating genotypes for either high yield potential or stable performance under drought stress. In order to select drought tolerant varieties of bread wheat an experiment was conducted in a randomized complete block design (RCBD) with two replications during the growing season 2014-2018. Eight drought tolerance indices including stress tolerance index (STI), geometric mean productivity (GMP), mean productivity index (MP), stress susceptibility index (SSI), tolerance index (TOL), yield index (YI), yield stability index (YSI) and drought resistance index (DI) were calculated and adjusted based on grain yield under drought years (Ys) and favorable years (Yp). Result of study showed significant positive correlation between grain yield in the stress condition (Ys) with indicators STI, GMP, TOL, MP, and DI, accordingly they are discriminating drought tolerant genotypes at the same manner. Wheat varieties Darkhan-172, Darkhan-72, Altaiskaya-325, Altaiskaya-70, Darkhan-181 has a high yield potential. Genotypes Darkhan-160, Arvin, Darkhan-144 most droughts tolerant and can be use in wheat breeding for improving drought resistance.Зусах зөөлөн буудайн сортуудыг ган тэсвэрийнүнэлэмжээр үнэлсэн дүнгээс Судалгаагаар манай оронд өргөн тариалагдаж байгаа өөрийн орны селекцээр гаргасан болон гадаадын нийт 20 сортонд ган тэсвэрийн индекс:стресс тэсвэрийн индекс (SТI), тэсвэрийн индекс (TOL),стресс мэдрэмжийн индекс (SSI), ган тэсвэрийн индекс (DI)-ээрүнэлгээ өгсөн. Зусах зөөлөн буудайн ургац ба ган тэсвэрийн индексүүдийн хооронд эерэг нягт хамааралыг тогтоосон. Чийгийн хангамж сайтай жилд потенциаль ургацаар буудайн эртийн болцтой Дархан-172, дунд-эртийн болцтой Дархан-72, Алтайская-325, Алтайская-70, дунд оройн болцтой Дархан-181 сортууд шалгарсан ба эдгээр сортуудыг селекцид хагас эрчимжсэн сорт гаргахад ашиглаж болно. Ган тэсвэр өндөртэй сортыг бий болгоходселекцид эртийн болцтой Дархан-160, дунд-эртийн болцтой Арвин, дунд оройн болцтой Дархан-144 сортуудыг эх материалаар ашиглаж болно. Зусах буудайн Дархан-144 сорт нь гадаад орчны нөхцөлд дасан зохицох чадвар сайтай сортоор шалгарав. Түлхүүр үг: болц,сорт, ургац, стресс, индекс